1979
DOI: 10.1159/000181703
|View full text |Cite
|
Sign up to set email alerts
|

Ten Years’ Survey of Dialysis-Associated Tuberculosis

Abstract: Tuberculosis associated with dialysis was studied at the Renal Unit of the Tokyo Medical and Dental University and Yokosuka Mutual Aid Hospital Kidney Center, in both of which the treatments of chronic renal failure are the same. There were 12 tuberculosis patients out of 367 patients on maintenance hemodialysis from January 1967 to December 1976, an incidence of 3.3%. This was 6–16 times greater than that in the general population of this country according to yearly statistics. The characteristics of dialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
4
3

Year Published

1982
1982
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 4 publications
(5 reference statements)
3
60
4
3
Order By: Relevance
“…The details of the 10 cases examined by QFT-2G are listed in Table 5 Previous studies reported a high frequency of cases of TB discovered in the first year of dialysis (3,4,13,19 HD (HD >1 year) T a b l e 3 . Ra d i o l o g i c a l Cl a s s i f i c a t i o n o f 1 6 P a t i e n t s wi t h P u l mo n a r y T u b e r c u l o s i s …”
Section: Qft-2gmentioning
confidence: 99%
“…The details of the 10 cases examined by QFT-2G are listed in Table 5 Previous studies reported a high frequency of cases of TB discovered in the first year of dialysis (3,4,13,19 HD (HD >1 year) T a b l e 3 . Ra d i o l o g i c a l Cl a s s i f i c a t i o n o f 1 6 P a t i e n t s wi t h P u l mo n a r y T u b e r c u l o s i s …”
Section: Qft-2gmentioning
confidence: 99%
“…[4,11] The incidence of TB in the various HD populations of the world (Canada, Poland, and Saudi Arabia) varies from 1.6% to 28%. [12][13][14] Acute infection with Mtb occurred in 7.9% of 224.954 patients in HD centers in the United States in 1995. [15] In Turkey, reported incidences of TB in HD patients have ranged from 6.1% to 23.6%.…”
Section: Introductionmentioning
confidence: 99%
“…Patients on chronic dialysis therapy are at an increased risk of being affected by tuberculosis (TB) [1, 2, 3, 4, 5], most likely because of the impaired cell-mediated immunity associated with end-stage renal disease [6, 7]. Periodical tuberculin skin tests or purified protein derivative (PPD) tests were suggested to detect infected TB patients [8].…”
Section: Introductionmentioning
confidence: 99%